Early Enteral Nutrition in Children With Acute Pancreatitis. Issue 3 (March 2016) - Abu-El-Haija, Maisam; Wilhelm, Rebecca; Heinzman, Christie; Siqueira, Bruna Nabuco Freire; Zou, Yuanshu; Fei, Lin; Cole, Conrad R.
Abstract : ABSTRACT: Nutrition is an integral part of acute pancreatitis (AP) management and is not adequately studied in pediatrics. The goal from the present study was to evaluate the effect of nutrition and fat content on the length of stay and pain severity in patients with AP. This is a retrospective review of our nutrition database between May 1, 2014 and December 1, 2014. Pain levels were similar between patients who were allowed to feed and patients kept nill per os. Higher fat intake grams per kilogram per day was associated with significantly lower pain scores. Early feeds are feasible in pediatric patients with AP. Pain was not increased in the group that had more fat in their diet.